2017
DOI: 10.1038/cddis.2017.561
|View full text |Cite
|
Sign up to set email alerts
|

MiR-106a-5p inhibits the cell migration and invasion of renal cell carcinoma through targeting PAK5

Abstract: MicroRNA-106a-5p (MiR-106a-5p), a small non-coding RNA, has been reported to be downregulated in astrocytoma, osteosarcoma and colorectal cancer. However, the expression levels and biological function in renal cell carcinoma (RCC) have not been studied yet. In this study, we found that the miR-106a-5p was significantly downregulated in RCC tissues and cell lines, and that overexpression of miR-106a-5p led to decreased cell metastasis ability in a xenograft model. Inhibition of miR-106a-5p in RCC cell lines alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 46 publications
4
82
0
Order By: Relevance
“…MiR‐28‐5p suppressed cell proliferation and migration by directly inhibiting RAP1B . MiR‐720 was significantly upregulated and had a clinical significance in RCC . The level of miR‐193a‐3p was evaluated in RCC patient serum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR‐28‐5p suppressed cell proliferation and migration by directly inhibiting RAP1B . MiR‐720 was significantly upregulated and had a clinical significance in RCC . The level of miR‐193a‐3p was evaluated in RCC patient serum .…”
Section: Discussionmentioning
confidence: 99%
“…23 MiR-720 was significantly upregulated and had a clinical significance in RCC. 25 The level of miR-193a-3p was evaluated in RCC patient serum. 16 However, the report about miR-193a-3p expression in RCC tissue and cell line was poor.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that miRNAs are key gene regulators and are abnormally expressed in ccRCC (20,44,45). The dysregulation of miRNAs has been demonstrated to affect the initiation and progression of ccRCC (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that p21‐activated kinase 5 (PAK5), the most recently identified member of the PAK family, plays an indispensable role in regulation of the cytoskeleton, microtubule stability and cell survival . Increasing lines of evidence suggest that PAK5 is an oncogenic protein that is commonly overexpressed in many cancer tissues and contributes to the progression of diverse cancers . Likewise, in human breast cancer, PAK5 has been shown to activate a PAK5–early growth response protein 1 (Egr1)–matrix metalloproteinase 2 (MMP2) pathway to control cell migration and invasion .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Increasing lines of evidence suggest that PAK5 is an oncogenic protein that is commonly overexpressed in many cancer tissues and contributes to the progression of diverse cancers. [7][8][9][10][11] Likewise, in human breast cancer, PAK5 has been shown to activate a PAK5-early growth response protein 1 (Egr1)-matrix metalloproteinase 2 (MMP2) pathway to control cell migration and invasion. 12 PAK5-directed GATA1 phosphorylation has been reported to induce epithelialmesenchymal transition in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%